THE MODULAR PRINCIPLE IN ORGANIZATION OF COURSES ON AUTOCAD - Natalya V. Kaygorodtseva; Mariya N. Odinets (Высшее образование в России)
If a person has a desire to remain an actual expert in the modern world, he has to update the knowledge, to study new directions and information technologies. Therefore there is a number of questions: How to carry out this process? Should an expert be engaged in self-education or complete courses in any educational center? The answers in many respects depend on the conditions and the quality of the educational process organized by training centers. The authors gave recommendations on application of an offered method of training to any software product. The main requirement to a choice of teaching methods is adaptation of courses to the requirements and practical problems of the customer. This article describes the teaching methods used in the educational center «Autodesk-OmSTU». The proposed method is based on a modular principle, easily expanded and modified for different courses.